2020
DOI: 10.1016/j.conctc.2020.100661
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief manualized intervention, Managing Cancer and Living Meaningfully (CALM), adapted to the Italian cancer care setting: Study protocol for a single-blinded randomized controlled trial

Abstract: Patients with advanced cancer suffer from psychosocial distress that may impair quality of life and that may be ameliorated by psychotherapeutic treatment. We describe here the methodology of a randomized controlled trial (RCT) to assess the effectiveness of a novel, brief, semi-structured psychotherapeutic intervention to reduce distress and increase well-being in patients with advanced or metastatic cancer. The intervention, called Managing Cancer and Living Meaningfully (CALM), was originally developed in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In addition to cognitively oriented and existential therapies, meaning-centred therapy has been identified as a targeted treatment for demoralisation (Kissane, 2017). The semi-structured intervention, 'Managing Cancer and Living Meaningfully' (Nissim et al, 2012), has shown a moderate effect size in ameliorating demoralisation in patients with high baseline death anxiety (Caruso et al, 2020;Rodin et al, 2018). Additionally, logotherapy, a therapy developed based on individuating life and existential meaning, has been demonstrated to be effective in the reduction of demoralisation in breast and gynaecological cancer patients (Sun et al, 2021).…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition to cognitively oriented and existential therapies, meaning-centred therapy has been identified as a targeted treatment for demoralisation (Kissane, 2017). The semi-structured intervention, 'Managing Cancer and Living Meaningfully' (Nissim et al, 2012), has shown a moderate effect size in ameliorating demoralisation in patients with high baseline death anxiety (Caruso et al, 2020;Rodin et al, 2018). Additionally, logotherapy, a therapy developed based on individuating life and existential meaning, has been demonstrated to be effective in the reduction of demoralisation in breast and gynaecological cancer patients (Sun et al, 2021).…”
Section: Future Directionsmentioning
confidence: 99%
“…They are both designed to help patients with cancer continue to find meaning in their lives after their illness and to maintain a sense of meaning at the end of life. CALM therapy, a semistructured, individualized, manualized psychological intervention, is specifically designed for patients with advanced cancer to reduce their suffering and increase their sense of well-being (Caruso et al, 2020a). CALM therapy can be understood simply as a combination of meaning-centered psychotherapy and active symptom management and has commonalities with meaning therapy (Lo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Active research on CALM has been conducted in several countries. However, unfortunately, most of the published articles on CALM are protocol studies (Caruso et al, 2020a; Lo et al, 2015), which do not allow access to the effect of CALM interventions on demoralization. Moreover, some national CALM protocols do not include demoralization as a measure (Caruso et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…As a pilot trial, the key objectives were to examine the feasibility of implementing the online CALM therapy in Chinese patients with metastatic breast cancer, while also allowing pilot test of potential treatment effects. Thus, a smaller sample size was selected similar as a former pilot study 23 . Mean difference (D) and standard deviation (SD) of efficacy evaluation results were often used as parameters for sample size calculations in randomized controlled studies.…”
Section: Methodsmentioning
confidence: 99%